Network of Actors and Public Sentiment in Indonesia’s Housing Savings Policy - Damu, Rheghy Pramudya; Irawati, Ira; Karlina, Nina (Ilomata International Journal of Social Science, 2026)
This research examines the discourse on the Public Housing Savings (Tapera) policy in Indonesia through an analysis of actor networks and public sentiment patterns. This research employed qualitative methods with a discourse analysis approach, using Discourse Network Analysis (DNA) to map relationships between actors, and NVivo to identify patterns of public sentiment. This research utilized secondary data collected from online news media, related regulations, and relevant scientific literature. The research findings indicate that actors involved in the public discourse regarding the Tapera policy include the government, business associations, celebrities, academics, professionals, labor groups, and the general public, who exhibit fragmented and ambivalent attitudes. The research implications indicate that lower-income groups are more vulnerable to the impacts of the Tapera policy. This situation has led to concerns and a narrative of distrust, thus increasing the tendency for pessimism towards the policy's implementation. Therefore, more adaptive and inclusive policy solutions are needed that better address the socio-economic dynamics of low-income communities (MBR).